THE FREQUENCY OF DENTAL DISEASES IN CHILDREN (LITERATURE REVIEW) - Khayitova Mokhinur Dzhuraevna (Лучшие интеллектуальные исследования, 2024)
The article presents the results of a literature review that reflect the current understanding of the somatogenic nature of dental pathology. The review included articles that highlight the results of clinical trials. Articles in Ukrainian, English and Russian were taken for study and analysis. The analysis of the articles was carried out taking into account the level of their evidence.